Utilisation and outcomes of Case‐based discussion in otolaryngology training. (April 2015) - Awad, Z.; Hayden, L.; Muthuswamy, K.; Ziprin, P.; Darzi, A.; Tolley, N.S.
<x xml:space="preserve">Abstract</x> Objectives To assess the reliability, validity and outcomes of Case‐based Discussion (CBD) in otolaryngology training. Design Retrospective database analysis. Setting National electronic database. Participants North London otolaryngology trainees. Main outcome measures We tested the tool's reliability along with its capacity to denote trainee progress. A score was calculated (cS) and compared across core (CT) and specialty trainees (ST) at all levels. The number of items rated as "development required" (D) was also examined. Results One thousand four hundred and fifty‐six CBDs were submitted by 46 trainees from 2007 to 2013, averaging 13.6 per trainee per year. Items relating to knowledge, management and judgement were more popular (98% usage), and better predictors of cS compared to other parameters (rs: +0.74, +0.70 and +0.72, respectively). CBD was found to be reliable (Cronbach's α = 0.848) and highly sensitive (99%), yet not specific. cS was significantly higher in ST than CT (95.3% ± 0.6 versus 88.7% ± 1.3). pS showed a similar pattern (3.15 ± 0.4 versus 2.0 ± 0.05) (P < 0.001). cS and pS increased from CT1 to ST8 (rs: +0.60 and +0.34, respectively). The number of D‐rated items decreased with increasing year of training. Conclusion Case‐based discussion is a reliable and valid tool in otolaryngology training. It is highly sensitive but not specific. Trainees should be encouraged to use it at all levels.